(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Aquaculture is a rapidly growing fisheries sector in India with an annual growth rate of over 7%. Inland fishing has an important role on the socio-economic development of the developing countries. Fishing is not only a source of income but also provider of necessary nutrients to our body. The fisheries sector plays a vital role in the economy by providing food & employment to millions of people. It is one of the fastest growing food production sectors in the world. The main objectives of the study is to explore the problems of inland fish cultivators in Trivandrum District. The present study has been based on primary data collected from the fishermen. The data has been collected with the help of the questionnaire and the respondents are selected by convenience sampling. The sample size for the study is 100 fishermen. It is found that the important problems of fish cultivators are weather, finance, labour, technical guidance, storage, transportation, quality issues etc. The problems of fish cultivators could be solved easily with the help of co-operative societies and Government.